Coordination of Body Segments During Turning in Healthy Adults - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Turning around to interact with the environment is a common activity of daily living. Coordination of body segments during turning is very important for the maintenance of upright posture. The aim of this review was to provide information about coordination of body segments during turning in health adults to serve as a yardstick for identifying turning problems in patients with neurological problems. Literature search was conducted through CINHAL, EMBASE, MEDLINE, and Google Scholar from inception to 2012 using the following search terms: coordination and turning, onset latency and turning, and peak velocity and turning. The present review has shown that turning to predictable targets results in a separate top to bottom sequence of onset of rotation of body segments, while turning to predictable targets results in a more simultaneous onset of rotation of the segments. On the contrary, the angle or direction a person turns to does not affect the sequence of rotation of body segments during turning. The peak velocity of the head was shown to be higher than that of the shoulder and pelvis when turning on-the-spot. The head was also shown to reach its peak velocity earlier than the shoulder and pelvis. However, the effect of the predictability of a target, turn angle, and turn direction on either the peak velocity or the time to reach the peak velocity has not been reported. The onset of rotation of body segments during turning while walking was shown to be in a top to bottom sequence. Alteration of the normal sequence of rotation of segments during turning could challenge the balance of an individual and may subsequently result into falls.